Encounter of Hybrid Learning: Design in Religious Moderation Learning - Andar Gunawan Pasaribu; Roy Charly H. P. Sipahutar; Eduward H. Hutabarat (LPPM IAKN Tarutung, 2021)
The parties in Indonesia are increasingly aware that exclusivity harms diversity, a breakthrough is needed that can bridge differences, especially in senior high school (SMA) in North Tapanuli Regency. Efforts have been made for this, for example with the encounter learning method for learning religious moderation, but this method cannot always be implemented due to various factors so that the results are not very effective, especially in developing the value of religious moderation among students. To obtain representative research data, this study uses the Research and Development (R & D) method. The purpose of this research is to produce a learning design of Encounter of Hybrid Learning that can be applied in a senior high school environment. From this study, it was found that the learning design of Encounter of Hybrid Learning was able to overcome the inhibiting factors that could not be answered in the learning encounter method but was able to foster the value of religious moderation among students.